A feather of stone - Tiernan, Cate (Tiernan, Cate. Balefire, 2005)
Seventeen-year-old twins Thais and Clio Allard finally discover one another after the tragic death of their father only to learn that the astonishing powers they possess will force them to complete a rite that will transform their lives forever.